Rotation of fullerene molecules in the crystal lattice of fullerene/porphyrin: C60 and Sc3N@C80. Issue 1 (9th November 2020) - Hao, Yajuan; Wang, Yaofeng; Spree, Lukas; Liu, Fupin
Abstract : The temperature driven rotation of the encapsulated Sc3 N cluster in a C80 fullerene cage was unraveled by variable temperature X-ray diffraction, which is significantly different from its analogues (Ho2 LuN/Lu3 N). Abstract : The dynamics of molecules in the solid-state is important to understand their physicochemical properties. The temperature-dependent dynamics of Sc3 N@C80 and C60 in the crystal lattice containing nickel octaethylporphyrin (NiOEP) was studied with variable temperature X-ray diffraction (VT-XRD). The results indicate that the fullerene cages (both C60 and C80 ) in the crystal lattice present stronger libration than the co-crystallized NiOEP in the temperature range of 100–280 K. In contrast to the fullerene cage, the Sc3 N cluster shows pronounced rotation roughly perpendicular to the plane of the co-crystallized NiOEP molecule driven by temperature. The obtained temperature dependent dynamic behavior of the Sc3 N cluster is different from that of Ho2 LuN and Lu3 N, regardless of their rather similar structure, indicating the effect of the mass and size of the metal ions.